Dramatic imaging changes of a biliary stricture within 8 months in a rare case - Ping Yue; Ping Yue; Ping Yue; Bing Bai; Bing Bai; Yanan Zhai; Yanyan Lin; Yanyan Lin; Wenbo Meng; Wenbo Meng; Xun Li; Xun Li; et al. (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Yue P, Bai B, Zhai Y, Lin Y, Meng W, Li X. Dramatic imaging changes of a biliary stricture within 8 months in a rare case. Turk J Gastroenterol 2020; 31(2): 180-3.